Effects of sewage sludge vermicompost and mineral fertilizer application on the aboveground biomass and yield of maize (Zea mays) - Syahmi Salleh,; Nik M. Majid,; Nor Azwady Abd. Aziz, (Penerbit Universiti Kebangsaan Malaysia, 2015)
Biological agriculture concept has been recently introduced to solve problems related to the continuous and excessive application of mineral fertilizers for crop production. This concept emphasizes the importance of combined use of organic and mineral fertilizers. Thus, this research was conducted to investigate the potential of sewage sludge vermicompost to substitute mineral fertilizer in maize planting. Treatments involved were mixture of vermicompost (VC) and mineral fertilizer (MF) in the following ratios of VC and MF: 100% VC (T1), 75:25 (T2), 50:50 (T3), 25:75 (T4), and 100% MF (T5) along with T6 (without fertilizer) as the control. Standard laboratory procedures were used to analyze nutrient and heavy metal concentrations in the vermicompost. The fresh yield and total aboveground dry matter biomass of T5 (239.34 gm plant-1 and 75.00 gm plant-1) were not significantly different with T3 (201.15 gm plant-1 and 73.61 gm plant-1) and T4 (226.49 gm plant-1 and 70.00 gm plant-1), respectively. These results showed that mixing 25% and 50% sewage sludge vermicompost with mineral fertilizer (T4 and T3) produced similar yield as the conventional rate of mineral fertilizer application (T5). Therefore, the amount of inorganic fertilizer for maize cultivation could be reduced.